“By browsing this site, you accept cookies”: Research on the cookie usage permissions of news sites in Türkiye - Murat Uluk (Connectist Istanbul University Journal of Communication Sciences)
While Internet cookies provide services for enhancing users’ experiences on websites, they have also become one of the leading tools for online surveillance. Particularly in recent years, increasing awareness levels about personal data, digital privacy studies, and legal regulations have raised concerns about the use of cookies. According to the legal framework, users must give explicit consent for the use of cookies that are not necessary for the functioning of a websites. From this point of view, this research examines Türkiye’s 50 most-visited news websitesbetween May 11, 2022, and May 19, 2022, to analyze their use of cookies. The data obtained show all news sites to have set non-necessary cookies on users’ devices without obtaining their explicit consent. One-third of the sites didn’t even provide any clarification statements regarding the use of cookies. Half of the sites that provide cookie usage statements were identified to claim visiting the site as a valid reason for setting cookies. The study is expected to raise awareness for the development of cookie usage systems that comply with both laws and ethical values of being honest, non-manipulative, and respectful to users and their choices.